AI Era: Using Hablo to Improve the Students’ English-Speaking Skills - Herlisya, Destia; Wiratno, Purna (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
English is no longer an exclusive language because it is now learned by people worldwide. In Indonesia, English plays a significant role in various domains, including society, business, politics, technological development, and education. However, Indonesian students often feel shy about speaking English when they believe they have not mastered the language. It is crucial for students to develop English-speaking skills to communicate effectively. Yet, speaking is a challenging skill to master. The third-semester students of STKIP PGRI Bandar Lampung in the academic year 2024/2025 faced several difficulties in speaking English, including a limited vocabulary, incorrect pronunciation, a lack of interlocutors, and minimal opportunities for extended interaction in English. To address these challenges, the researchers used Hablo, an application that integrates artificial intelligence features with English language learning. This study employed classroom action research conducted over two cycles. The results demonstrated significant improvements in both the students' speaking skills and their learning activities across the pre-cycle, Cycle I, and Cycle II. The mean speaking test score increased from 64.8 in the pre-cycle to 67 in Cycle I and further to 77.75 in Cycle II. The findings indicate that using Hablo positively impacts students' speaking abilities and engagement in learning. This research highlights the potential of integrating AI-powered tools, like Hablo, into English language teaching to address students' specific challenges in speaking. The study suggests that such tools can enhance vocabulary acquisition, improve pronunciation, and provide opportunities for interactive learning. These findings emphasize the importance of leveraging technology to create engaging and effective language-learning environments